Հայոց եկեղեցու անդամագրությունն ըստ «Արևորդիների դարձի մասին» Ս․ Ներսես Շնորհալու թղթի - Բաղումյան, Զաքարիա Ծ․ Վրդ․
St. Nersēs the Gracious’ famous epistle “Conversion of the Sons of Sun” is a singular source, rare in its treatment of the identity of this abstruse religious sect. The letter reveals that the clergy of the city of Samosata, including representatives of the Sons of the Sun, appealed to the Armenian Patriarch to accept them into the Armenian Church. According to St. Nersēs, the Sons of Sun are ethnic Armenians who were not baptized by St. Gregory the Illuminator, instead resembling the Paulicians in terms of dogma. St. Nersēs describes in detail the order of acceptance into the Armenian Church and the necessary liturgical steps: public renunciation of Satan and of all previous delusions, confession of the orthodox faith, entrance into the church, Holy Baptism and, finally, the anointing the neophyte with Holy Myron. This section of the letter is followed by the issuance of practical advice for priests and the newly baptized. In the article, the liturgical steps and the process of acceptance into the Church cited by St. Nersēs the Gracious, are compared with the ancient baptismal rite of the Armenian Church, several handwritten and printed Mashtots‘ and the accepted theological approaches to the issue of the time. The letter once again reveals the character of the spiritual and beloved father who is zealous in fostering the unity of his flock and the union of the faith. Известное послание Святого Нерсеса Благодатного «Об обращении сынов солнца» – один из редких армянских источников, содержащих сведения об этой ереси. Духовенство, представители сынов солнца и другие жители города Самосаты обратились к Армянскому Католикосу с просьбой принять их в лоно Церкви. Согласно Св. Нерсесу Благодатному, сыны солнца – этнические армяне, говорящие на армянском языке, которые не были крещены Святым Григорием Просветителем; по своим верованиям они были близки к павликианам. Св. Нерсес в своем послании подробно описывает порядок оглашения и воцерковления: публичное отречение от прежних заблуждений и сатаны, исповедание православной веры, вхождение в церковь, Святое Крещение и Миропомазание, за которыми следуют практические наставления священникам и новообращенным. Описанные в послании Св. Нерсеса Благодатного ступени воцерковления сопоставлены с сохранившимся древнейшим чином Святого Крещения, некоторыми рукописными и печатными Требниками и богословскими воззрениями данного времени. В послании перед нами вновь предстает образ духовного отца, любящего свою паству и неустанно трудящегося ради ее единства и единства веры.
Keywords: Հայոց եկեղեցի